2019
DOI: 10.3390/pr7070408
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variations of Bacterial Communities of an Anaerobic Lagoon-Type Biodigester Fed with Dairy Manure

Abstract: Anaerobic digestion technology is being widely employed for sustainable management of organic wastes generated in animal farms, industries, etc. Nevertheless, biodigester microbiome is still considered a “black box” because it is regulated by different physico-chemical and operational factors. In this study, the bacterial diversity and composition in different sites of a full-scale lagoon type biodigester (23,000 m3) fed with dairy manure, viz., the influent, beginning, middle, final and effluent were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
(51 reference statements)
1
3
0
Order By: Relevance
“…The Proteobacteria, the Bacteroidetes, the Firmicutes, the Actinobacteria, the Synergistetes, the Euryarchaeota, and Cloacimonetes were the dominant phyla in WWTP Marrakech. These data are similar to those previously obtained using marker gene-based analysis [39,40,52,53,55,[57][58][59]. At the OTU level (Figure 3), OTU 1 (Firmicutes), OTU 2 (Cloacimonetes), and OTU 3 (Bacteroidetes) were the most abundant of the four digesters.…”
Section: Discussionsupporting
confidence: 89%
“…The Proteobacteria, the Bacteroidetes, the Firmicutes, the Actinobacteria, the Synergistetes, the Euryarchaeota, and Cloacimonetes were the dominant phyla in WWTP Marrakech. These data are similar to those previously obtained using marker gene-based analysis [39,40,52,53,55,[57][58][59]. At the OTU level (Figure 3), OTU 1 (Firmicutes), OTU 2 (Cloacimonetes), and OTU 3 (Bacteroidetes) were the most abundant of the four digesters.…”
Section: Discussionsupporting
confidence: 89%
“…Members of Latescibacterota (previously WS3 and candidate phylum Lastescibacteria) were first discovered in a hydrocarbon-contaminated aquifer and have since been found in marine sediments, hydrothermal vents, soil and other hydrocarbon-contaminated environments (Farag et al 2017 ). Recently, members of this clade were shown to encode for fermentation (García-Lozano et al 2019 ) and anaerobic hydrocarbon degradation (Dombrowski et al 2017 ), still none have been reported to encode the capacity for aerobic methane oxidation. The Latescibacterota in this study all have pmoA , SDR and ALDH, although most of those genes recruited minimal DNA and RNA reads.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Lourenco et al 42 used PICRUSt for a comparison of the microbiota of the beef cattle both ruminal and fecal. Several authors 43 46 have specifically focused on its application in biogas processes.…”
Section: Introductionmentioning
confidence: 99%